Comparative leaf anatomy of ten Nepenthes L. species (Nepenthaceae) from Peninsular Malaysia - Mohd N. GHAZALLI; Amin A. TAMIZI; Dome NIKONG; Muhammad I. MAT ESA; Edward E. BESI; Salmaniza SALLEH; Noraini TALIP; A. LATIFF (Notulae Scientia Biologicae, 2021)
The genus Nepenthes (Nepenthaceae) in Peninsular Malaysia includes fourteen species that can be found from the sea-level to over 1000 m in the mountains. Our observation indicated that Nepenthes can be found in five major habitat types: specifically in tropical lowland evergreen rain forest, heath forest, peat swamp forest, montane forest, and limestone forest. Their leaves have several anatomical characters that remain underexplored. There were specific differences between species that could be potential identification characters. The following anatomical characteristics were explored for their diagnostic value and comprised of ten distinct anatomical characteristics in Nepenthes, viz., density and stomatal index (SI), hypodermis cell – cell layers, occurrence of fiber groups mixed with the hypodermis cells, adaxial cuticle thickness, vascular bundle arrangement, midrib outline shape, venation plasticity, druses appearance and appendage/trichome type.